Theoretical study of optical properties of non-polar BAlGaN/AlN quantum wells lattice-matched to AlN. (March 2019) - Park, Seoung-Hwan; Ahn, Doyeol
Abstract: Light emission characteristics of non-polar ultraviolet (UV) B x Al y Ga1− x − y N/AlN quantum well (QW) structures lattice-matched to AlN substrate were theoretically investigated using the multiband effective-mass theory. The peak intensity of the non-polar BAlGaN/AlN QW structure lattice-matched to AlN is found to be much larger than that of the c-plane BAlGaN/BAlGaN QW structure lattice-matched to AlN. Also, the lattice-matched BAlGaN/AlN QW structure shows a large polarization ratio and its value changes from 0.7 to 0.9 in an investigated range of carrier density. We expect that non-polar BAlGaN/BAlGaN QW structures lattice-matched to AlN could be used as a UV light source with a higher crystal quality. Highlights: We studied the optical properties of non-polar BAlGaN/AlN quantum wells lattice-matched to AlN. It shows much larger light intensity than the c-plane lattice-matched QW structure. The optical matrix element greatly depends in the in-plane wave vector. The polarization ratio strongly depends on carrier density. It has a large polarization ratio (0.7–0.9).